2004
DOI: 10.1080/10446670410001722203
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IL‐1β and TNF‐α Secretion from Resting and Activated Human Immunocytes by the Homeopathic Medication Traumeel® S

Abstract: Traumeelw S (Traumeel), a mixture of highly diluted (10 21 -10 29 ) extracts from medicinal plants and minerals is widely used in humans to relieve trauma, inflammation and degenerative processes. However, little is known about its possible effects on the behavior of immune cells. The effects of Traumeel were examined in vitro on the ability of resting and PHA-, PMA-or TNF-a-activated human T cells, monocytes, and gut epithelial cells to secrete the prototypic pro-inflammatory mediators IL-1b, TNF-a and IL-8 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
2
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 10 publications
2
41
2
7
Order By: Relevance
“…10 In the in vitro setting, Traumeel S has demonstrated antiinflammatory properties, inhibiting the proinflammatory mediators interleukin (IL)-1b, tumor necrosis factor (TNF)-a, and IL-8 in resting and activated human immunocytes. 11 Lussignoli et al demonstrated a decrease of IL-6 as well, in a rat paw inflammation model following treatment with Traumeel. 12 The purpose of the current study was to test the effect of Traumeel on cytokine production in an in vivo setting, using a cecal ligation and puncture (CLP) sepsis model in rats, a well-established animal model for the production of inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 98%
“…10 In the in vitro setting, Traumeel S has demonstrated antiinflammatory properties, inhibiting the proinflammatory mediators interleukin (IL)-1b, tumor necrosis factor (TNF)-a, and IL-8 in resting and activated human immunocytes. 11 Lussignoli et al demonstrated a decrease of IL-6 as well, in a rat paw inflammation model following treatment with Traumeel. 12 The purpose of the current study was to test the effect of Traumeel on cytokine production in an in vivo setting, using a cecal ligation and puncture (CLP) sepsis model in rats, a well-established animal model for the production of inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 98%
“…Another drug, Traumeel S, was shown to inhibit the production of interleukin-1, TNF (tumor necrosis factor)-a, and interleukin-8 by human T cells and monocytes in culture. 16 Phase 6 and Flu Terminator, 2 homeopathic formulations, which contain a combination of homeopathic drugs, were reported to stimulate the production of proinflammatory and anti-inflammatory cytokines by human leukocytes. 17 These results indicate that homoeopathic medicines have the capacity to inhibit cell proliferation and reduce animal tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale of using Traumeel ® in this study is supported by evidence suggesting the inhibitory role in pro-inflammatory mediators from immune cells (Porozov et al, 2004), the synergistic action of the ingredients and the acceleration of the healing process (Lussignoli et al, 1999). It has been shown that between dilutions of 10 -1 to 10 -7 , Traumeel ® has a selective inhibitory effect on some pro-inflammatory mediators, such as IL-1β, TNFα, and IL-8 (Porozov digital flexor tendons (Bosch et al, 2010).…”
Section: Discussionmentioning
confidence: 62%